Drawing masterclass : 100 creative techniques of great artists - Noble, Guy (Artist) (London: Thames&Hudson., 2017)
"Gorgeously illustrated and practical, this guide to the art of drawing employs a close analysis of great works to reveal techniques and lessons that will help practitioners at every level. The art of drawing is an essential skill for any artist. This beautifully produced book uses 100 great works on paper as its lessons. Each spread features a reproduction of one work, and offers invaluable lessons about the approaches and techniques the artist used. Organized into chapters on nudes, figures, landscapes, still life, heads, fantasy, and abstraction, the book breaks down the featured works in different ways. For instance it explores how differences in tone and shadow bring life to a standing figure and how many different weights of line can be achieved with one crayon. In addition, readers can learn from the artist's own words in quotations drawn from interviews and archival materials. There is no better way to learn a skill than from the masters. Beginning and experienced artists can learn from masters as diverse as Kandinsky, Rubens, Monet, da Vinci, Basquiat, Beckman, and Miro, while professionals in the field will find great value in side-by-side comparisons of works from different genres and eras"--www.amazon.com.
Includes index.
Keywords: Artet boterore; Arti vizual-vizatimi; Manual -- Artiste boterore; Drawing -- Technique-teknika -- Handbooks, manuals, etc; Drawing -- Technique-teknika; Drawing -- Technique; Vizatimi-historia-teknika-keshilla krijuese-manual; Handbooks and manuals